PELATIHAN BAHASA INGGRIS PEMANDU WISATA LOKAL DI DESA KAPAL - Sudipa, I. N.; Rajeg, I. M.; Laksminy, L. P. (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Vol 13, No. 2 (2014), 2014)
The training of Practical English for local guides was conducted in Kapal-Mengwi. The materials focused on the language functions, among others: Greeting, Apologizing and Requesting. Through the methods: orientation, drills, feedback and continuation, the participants-Pokdarwis members managed to use them practically. The only obstacle they might face is the pronunciation of [th]. Keywords: Pokdarwis, pronunciation